Mengukur Peran Pembiayaan Bermasalah Bank Umum Syariah Dalam Upaya Meningkatkan Profitabilitasnya Di Situasi Pandemic Covid-19 - Moegiri, M; Hidayah, Rini; Dwi Andayani, Tutut; Yohani, Yohani (Neraca, 2024)
This study aims to determine whether there is an effect of Musyarakah Financing, Capital Adequacy Ratio (CAR) and Financing to Deposit Ratio (FDR) on the Profitability of Islamic Commercial Banks after moderating the Financing to Deposit Ratio (FDR) sourced from www.ojk.go.id from 2020-2022 with a sample of 11 (eleven) Islamic commercial banks. The data management of this study used IBM SPPS 26 to test the hypothesis using the t test and MRA Analysis (Moderated Regression Analysis). The results of this study indicate that musyarakah financing has a negative effect on Return on Assets (ROA), while CAR and FDR have no effect on profitability (ROA) at Islamic Commercial Banks before being moderated. After the MRA analysis test was conducted, it was found that NPF was unable to moderate the effect of musyarakah financing on ROA, NPF was able to moderate the effect of CAR on ROA, and NPF was unable to moderate the effect of FDR on ROA. While the results of the simultaneous test state that musyarakah financing, CAR, FDR with or without NPF moderation jointly affect the profitability (ROA) of Islamic commercial banks. REFERENSI Ghozali, Imam. 2011. Aplikasi Anlisis Multivariante Dengan Program IMB SPSS 25. Semarang: Badan Penerbit Universitas Diponegoro. IAI. 2017. Standar Akuntansi Keuangan Syariah. Jakarta: IAI. Moegiri, M, Tutut Dwi Andayani, and S Saebeni. 2022. “ANALISIS KOMPARATIF SEBELUM DAN SAAT PANDEMI COVID 19 BANK UMUM SYARIAH.” Neraca 18(1): 1–12. Nur’aini Ihsan, Dwi. 2013. Analisis Laporan Keuangan Perbankan Syariah. Jakarta: UIN jakarta Press. Pritadyana, Mella, Nik Amah, and Maya Novitasari. 2019. “PENGARUH FDR DAN NIM TERHADAP ROE DENGAN NPF SEBAGAI VARIABEL MODERASI.” Sanusi, Anwar. 2013. Metodelogi Penelitian Bisnis. Jakarta: Salemba Empat. “Statistik Perbankan Syariah- Desember 2022..Xlsx.” “Surat Edaran OJK No. 10_SEOJK.03_2014_Penilaian Tingkat Kesehatan BUS Dan UUS.Pdf.” Wiroso. 2011. Akuntansi Transaksi Syariah. Jakarta: Ikatan Akuntan Indonesia. Yulyani, Evita, and Nana Diana. 2021. “Pengaruh CAR Dan FDR Terhadap Pembiayaan Murabahah Dengan NPF Sebagai Variabel Moderating.” Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah 7(1): 21. www.ojk.go.id